Kebermaknaan Hidup Bagi Narapidana Yang Belum Menikah Di Rutan Kelas IIb Batusangkar - Hakimi, Laras; Sisrazeni, Sisrazeni (Batanang : Jurnal Psikologi, 2022)
Based on the results of the study, it was found that the meaning of life of unmarried prisoners was seen from the fulfillment of the meaningfulness of life dimensions in which the three respondents could reach the stages of meaningfulness of life. The three respondents reached the meaning of their life after going through processes consisting of the stage of suffering or suffering, the stage of self-acceptance, the stage of changing attitudes, the stage of finding the meaning of life, the stage of self-bonding, and the stage of life which means that the respondent is more appreciative of the values of appreciation, namely by making family as the goal of life. This appreciation is manifested differently by the three respondents. In the first and third respondents, N and R chose to direct the meaning of their lives to become people who obey God and make their parents proud, the second respondent, SE chose to direct the meaning of their lives for their families and education.Keyword: The Meaning of Life, Prosoners, State Prison